THE JURISDICTION OF THE CHOSEN JUDGE (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
In today’s private international law, the parties may choose freely the jurisdiction where their dispute shall be resolved. This is usually made through the means of a jurisdiction clause inserted in their contract. The European Law confers exclusive jurisdiction to the chosen judge, which means, in principle, that the parties are not allowed to refer the matter to a court other than the one provided for in the choice of court agreement. In our paper, we will analyse the consequences of this qualification of jurisdiction as exclusive and the means by which it is protected in the European law, under the Brussels I bis Regulation.The protection of the jurisdiction agreed by the parties previously to the dispute is, nevertheless, not absolute as it has its limits. The European law does not provide remedies for all the situations of breach of jurisdiction that may appear and we will present a couple of situations where the expectations of a party may be infringed by the tactics of its adversary in the dispute.
Keywords: Choice of court, Regulation no. 1250/2012, exclusive jurisdiction, international lis pendens, recognition and enforcement of foreign awards